Explosão de imagens no livro Películas, de Luís Miguel Nava - Santos, Nádia Rodrigues dos [UNESP] (2015)
Portuguese poet of the 1970 generation, Luís Miguel Nava composed a book know for its power and the consequent impact caused by a language that is founded by an explosion of images that succeed themselves in the poem's composition, which stem mainly from metaphors that are build based on the thematic axes that are repeated in several textual levels. From a formal perspective, navian writing consummates the conciliation between two movements. On one hand, it retrieves aspects of poetry tradition, recovering images inherited from several predecessors, of the most diverse origins and lineages. From a further poet like Bashô, through some masters of modernity, like Baudelaire, and even portugueses like Eugênio de Andrade and many others. On the other hand, it shows special attention to contemporary lyrical tendencies by not closing itself to post-modern questions. Therefore, the hassle into classifying the poet to a group or tendency, which leads to the conclusion that navian work should be envisaged as a manifestation of the post-modern pluralism by presenting traditional elements together with modern, neoavant- garde and contemporary aspects. By understanding poetry as a precise and systematic exercise that is attached to its relation with reality, whether by memory or by observing the world around, the poet presents an unusual domain over formal techniques and procedures, besides an elevated degree of critical conscience. Approaching a selected corpus composed by 16 poems from the book Películas (1976), this work tried, through poetry analysis elaborated with the support of theoretical texts about the focalized questions and the critical collection of the poet, to comprehend the main procedures adopted by Luís Miguel Nava while elaborating his poems, specially, when creating his unused poetical images